Experimental study of droplet evaporation boiling curve using stainless steel - Goh, Wan Gin (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Boiling heat transfer has received considerable attention during the past decade, the inpetus for the increased effort coming form modern development in technology.The heat transfer to a water droplets impecting on a hot surface is used for various purpose such as cooling processes in steel production industries and emergency core cooling in nuclear power plants.